Fast, but not slow, familiarity is preserved in patients with amnestic mild cognitive impairment. (April 2015) - Besson, Gabriel; Ceccaldi, Mathieu; Tramoni, Eve; Felician, Olivier; Didic, Mira; Barbeau, Emmanuel J.
Abstract: Recognition memory – affected early in the course of Alzheimer Disease (AD) – is supposed to rely on two processes: recollection (i.e., retrieval of details from the encoding episode) and familiarity (i.e., acontextual sense of prior exposure). Recollection has repeatedly been shown to be impaired in patients with amnestic Mild Cognitive Impairment (aMCI) – known to be at high risk for AD. However, studies that evaluated familiarity in these patients have reported conflicting results. Here, we assessed familiarity in single-domain aMCI patients ( n = 19) and healthy matched controls ( n = 22). All participants underwent a classic yes/no recognition memory paradigm with confidence judgements, allowing an estimation of familiarity and recollection similar to the approach used in previous studies. In addition, they underwent a novel speeded recognition memory task, the Speed and Accuracy Boosting procedure, based on the idea that familiarity is fast and hence that fast answers rely on familiarity. On the classic yes/no task, aMCI patients were found to have impaired performance, reaction times, recollection and familiarity. However, performance and reaction times of aMCI patients did not differ from that of controls in the speeded task. This is noteworthy since this task was comparatively difficult for control subjects. This dissociation within familiarity suggests that a very basic component of declarative memory, probably at the interface between implicit and explicit memory, may be preserved, or possibly released, in patients with aMCI. It is suggested that early subprocesses (e.g., fluency based familiarity) could be preserved in aMCI patients, while delayed ones (e.g., conceptual fluency, post-retrieval monitoring, confidence assessment, or even access to awareness) may be impaired. These findings may provide support for recent suggestions that familiarity may result from the combination of a set of subprocesses, each with its specific temporal signature.